2016
DOI: 10.1093/humupd/dmw028
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian ageing: the role of mitochondria in oocytes and follicles

Abstract: A fuller understanding of the involvement of mitochondria in cases of infertility linked to ovarian ageing would contribute to a better management of the disorder in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
315
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 423 publications
(324 citation statements)
references
References 279 publications
7
315
0
2
Order By: Relevance
“…Alterations in the mtDNA, which are reflected by the change of its copy number and its mutation, have been reported to be involved in a series of diseases and in organ dysfunction (4). Several studies have reported that the alterations of mtDNA are involved in the maturity, aging and lesion formation in the ovary (12,13). Mutations in mtDNA can cause the abnormally expression of oxidative phosphorylation complex and abnormal transfer RNAs, which may be associated with polycystic ovarian syndrome patients (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations in the mtDNA, which are reflected by the change of its copy number and its mutation, have been reported to be involved in a series of diseases and in organ dysfunction (4). Several studies have reported that the alterations of mtDNA are involved in the maturity, aging and lesion formation in the ovary (12,13). Mutations in mtDNA can cause the abnormally expression of oxidative phosphorylation complex and abnormal transfer RNAs, which may be associated with polycystic ovarian syndrome patients (12).…”
Section: Discussionmentioning
confidence: 99%
“…Devine et al (14) also reported that ~20% of patients consulting for infertility presented signs of premature ovarian aging. In addition, ovarian aging is associated with reduced oocyte mtDNA content and mitochondrial dysfunction (13). Numerous studies have reported that the mtDNA content in the oocytes of aged women or of women with a diminished ovarian reserve is significantly lower when compared with that of young patients or those with a normal ovarian reserve (6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…112 Subsequently, more than 50 successful live births have been achieved with this method. 113 However, due to lack of adequate experimental data and the potential risk associated with the transmission thirdparty genetic material, the US Food and Drug Administration (FDA)…”
Section: Mitochondrial Transfermentioning
confidence: 99%
“…If any disorder occurs in any part of the process of mutual regulation between granulosa cells and oocytes, it will interfere with the reproductive process and further affect reproduction (Nagyova, Kalous, & Nemcova, ). Although the emergence of assisted reproductive technology (ART) has made great progress in the treatment of infertility, some infertility patients are still unable to obtain offspring through ART (Chen & Zhou, ; Giuliani et al, ; May‐Panloup et al, ). One of the main reasons is that the molecular mechanism of the interaction between granulosa cells and oocytes is not completely understood (Chang, Qiao, & Leung, ).…”
Section: Introductionmentioning
confidence: 99%